The Important Role Of Evaluation Of Citizenship Education Learning At Al-Hidayah Primary School In Increasing Students' Social Awareness - Sari, Kartika; Siregar, Delisma; Manihuruk, Waldio; Yus, Anita; Lubis, Wildansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This research reviews the important role of learning evaluation in citizenship education at Al-Hidayah Elementary School, with a focus on increasing students' social awareness. Through a qualitative research approach, this study aims to gain an in-depth understanding of how learning evaluation contributes to the formation of students' social awareness. The qualitative research steps used include data collection through interviews with teachers and students, classroom observations, document analysis, and case studies at SD Al-Hidayah. The research results show that learning evaluation is not only useful for measuring student academic achievement, but also helps in understanding student progress at SD Al-Hidayah in understanding the concepts of citizenship and social values. Through evaluation, teachers can improve teaching, provide relevant feedback to students, and monitor individual and class progress. The results of this research can be a basis for developing more effective learning programs in promoting students' social awareness at Al-Hidayah Elementary School.